2021
DOI: 10.1111/aji.13425
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained recurrent miscarriages: predictive value of immune biomarkers and immunomodulatory therapies for live birth

Abstract: Introduction: Recurrent miscarriages are defined as three or more early miscarriages before 12 weeks of gestation. The aim of this study was to describe a cohort of women with unexplained recurrent miscarriages, evaluate several potential biomarkers of immune origin, and describe the outcome of pregnancies under immunomodulatory therapies.Methods: Women having a history of at least 3 early miscarriages without any etiology were recruited from 3 university hospitals.Results: Among 101 women with recurrent misca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…About 1∼3% of women experience early recurrent implantation failure; about 50% of patients are associated with unexplained RIF [ 21 – 23 ]. Many studies have found that the cytokine balance of Th1/Th2/Th17/regulatory T cells (Treg) plays an important role in the maintenance of embryo implantation and normal pregnancy, especially for unexplained RIF [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 1∼3% of women experience early recurrent implantation failure; about 50% of patients are associated with unexplained RIF [ 21 – 23 ]. Many studies have found that the cytokine balance of Th1/Th2/Th17/regulatory T cells (Treg) plays an important role in the maintenance of embryo implantation and normal pregnancy, especially for unexplained RIF [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is the first time to evaluate the efficacy and maternal and child health of the CAM therapy (ZYF with auricular acupressure) for the RIF and a correlation between serum T lymphocyte expression and the use of the CAM therapy in IVF cycles has been reported. 4 Evidence-Based Complementary and Alternative Medicine About 1∼3% of women experience early recurrent implantation failure; about 50% of patients are associated with unexplained RIF [21][22][23]. Many studies have found that the cytokine balance of 1/ 2/ 17/regulatory T cells (Treg) plays an important role in the maintenance of embryo implantation and normal pregnancy, especially for unexplained RIF [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, I would like to congratulate you on the publication of the article entitled Unexplained Recurrent Miscarriages: Predictive Value of Immune Biomarkers and Immunomodulatory Therapies for Live Birth, by Kolanska et al 1 Medical centers are characterized by the plurality of its audience, with personalized treatments and outcomes of non-homogeneous populations. Although it is not possible to make a population inference from a longitudinal observational study due to the heterogeneity of its sample, it seems to be very helpful in the practical reality.…”
Section: Unexplained Recurrent Miscarriages: Predictive Value Of Immu...mentioning
confidence: 99%
“…The Kolanska et al 1 study defined spontaneous miscarriage as miscarriage before 12 weeks gestation, with the same partner. Regardless of the conceptual definition on recurrent miscarriage, which varies along studies, the risk of miscarriage increases independently with maternal age and the number of previous losses.…”
Section: Unexplained Recurrent Miscarriages: Predictive Value Of Immu...mentioning
confidence: 99%